A Modified Chinese Herbal Decoction (Kai-Xin-San) Promotes NGF-Induced Neuronal Differentiation in PC12 Cells via Up-Regulating Trk A Signaling - Yan, Lu; Wei, Min; Gong, Amy G.; Song, Pingping; Lou, Jianshu; Bi, Cathy W.; Xu, Sherry L.; Xiong, Aizhen; Dong, Tina T.; Tsim, Karl W. (Frontiers in Cell and Developmental Biology, 2017)
Kai-Xin-San (KXS), a Chinese herbal decoction, has been applied to medical care of depression for thousands of years. It is composed of two functional paired-herbs: Ginseng Radix et Rhizoma (GR)-Polygalae Radix (PR) and Acori Tatarinowii Rhizoma (ATR)-Poria (PO). The compatibility of the paired-herbs has been frequently changed to meet the criteria of syndrome differentiation and treatment variation. Currently, a modified KXS (namely KXS2012) was prepared by optimizing the combinations of GR-PR and ATR-PO: the new herbal formula was shown to be very effective in animal studies. However, the cellular mechanism of KXS2012 against depression has not been fully investigated. Here, the study on KXS2012-induced neuronal differentiation in cultured PC12 cells was analyzed. In PC12 cultures, single application of KXS2012 showed no effect on the neuronal differentiation, but which showed robust effects in potentiating nerve growth factor (NGF)-induced neurite outgrowth and neurofilament expression. The potentiating effect of KXS2012 was mediated through NGF receptor, tropomyosin receptor kinase (Trk) A: because the receptor expression and activity was markedly up-regulated in the presence of KXS2012 and the potentiating effect was blocked by k252a, an inhibitor of Trk A. Our current results in cell cultures fully support the therapeutic efficacy of KXS2012 against depression.